Acceptance of SARS-CoV-2 vaccines by liver transplant recipients and candidates - Reuken, Philipp A.; Albers, Stefanie; Rauchfuss, Falk; Strnad, Pavel; Settmacher, Utz; Trautwein, Christian; Stallmach, Andreas; Bruns, Tony (Zeitschrift für Gastroenterologie, 2021)
Guidelines recommend vaccination against SARS-CoV-2 in transplant recipients, candidates, and their household contacts. However, little is known about the acceptance of COVID-19 vaccines in these groups.In March 2021, we surveyed 826 liver transplant recipients, candidates, and their household contacts to determine acceptance rates and factors influencing the acceptance of the COVID-19 vaccine; 341 patients (40%) and 237 household contacts (28%) returned the questionnaire. Ninety percent of patients returning the survey reported they were willing to receive the vaccine within the next 6 months or had already started vaccination. Only 2% of patients and 4% of household contacts reported refusing the vaccine, and 8% of patients and 9% of household contacts wanted to postpone vaccination because of concerns about side effects. Having received the influenza vaccine in the last 2 seasons was the strongest indicator of acceptance to receive the SARS-CoV-2 vaccine within 6 months (odds ratio 5.11; 95% confidence interval 2.43–10.74; p < 0.001). Thirty-two percent of responding patients reported fear of side effects as a reason for having refused vaccination before.Although the acceptance of the SARS-CoV-2 vaccine was particularly high among German liver transplant recipients, candidates, and household contacts in this survey, transplant physicians are encouraged to discuss safety concerns with patients who have refused the seasonal influenza vaccine in the past.
Keywords: LTX; Impfung; SARS-CoV-2; COVID-19; Influenza